USM STUDENTS BRING CHEERS TO AUTISTIC CHILDREN - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 27 February 2017 – The Social Work Club at Universiti Sains Malaysia (USM) recently held a programme with autistic kids at the National Autism Society (NASOM) premises in Butterworth, Penang.